Direct Z-scheme among Niobium Pentoxide and Poly(heptazine imide) for NH3 Photoelectrosynthesis under Ambient Conditions - Blaskievicz, Sirlon F.; Freitas Teixeira, Ivo; Mascaro, Lucia Helena; Ferreira de Brito, Juliana [UNESP] (Wiley, 2023)
There is a crescent need to improve well-known processes to environmentally friendly options, and NH3 production is not an exception. Herein, we describe the photoelectrochemical nitrogen reduction reaction under a carbon nitride, the poly(heptazine imide) (PHI) using mild conditions for NH3 synthesis. For this purpose, PHI was combined with Nb2O5 nanotubes, leading to a new photocathode with a charge transfer process in a Z-scheme structure. The photoelectrocatalytic N2 reduction was carried out in Nb2O5Nt/PHI using solar-simulated radiation and with an applied bias of −0.3 VAg/AgCl. The PHI presence in the photocathode showed not only superior stability compared to bare Nb2O5, but also an ammonia generation rate of 0.156 mmol L−1 h−1 cm−2, which is about 10-fold higher than the amount obtained with niobium oxide alone. The mild and green conditions employed for ammonia generation place the obtained photocathode as a promising option for the currently used Haber-Bosch process.
Keywords: Ammonia synthesis; N2 reduction; Photoelectrocatalysis; Poly(Heptazine Imide); Polymeric carbon nitrides